All‐Epitaxial Bulk Acoustic Wave Resonators. Issue 7 (5th March 2020) - Miller, Jeffrey; Wright, John; Xing, Huili Grace; Jena, Debdeep
Abstract : There is a growing interest in the exploration of the nitride material family for radically scaled, high frequency, ultrasonic devices by epitaxial growth techniques. Furthermore, the introduction of epitaxial growth techniques to conventional nitride‐based acoustic technology opens the door to exciting new families of structures for phonon confinement. As the need for higher frequency communications increases, both piezoelectrics and electrodes must scale to smaller dimensions. It has recently become possible to epitaxially grow single‐crystalline, wurtzite AlN/NbN piezoelectric/metal heterostructures. The epitaxial NbN films maintain high crystalline quality and electrical conductivity down to several nanometers thickness. This study demonstrates preliminary results on the feasibility of an all‐epitaxial bulk acoustic wave technology by growing and characterizing the radio frequency (RF) properties of an epitaxial AlN/NbN heterostructure. Abstract : There is a growing interest in the exploration of the nitride material family for radically scaled, high frequency, ultrasonic devices by epitaxial growth techniques. This study demonstrates preliminary results on the feasibility of an all‐epitaxial bulk acoustic wave technology by growing and characterizing the radio frequency (RF) properties of an epitaxial AlN/NbN heterostructure on 6H–SiC substrate.